Happiness Is the Wrong Metric: A Liberal Communitarian Response to Populism (excerpt) - Etzioni, Amitai (Journal of Economic Sociology, 2024)
In his Happiness is the Wrong Measure: A Liberal Communitarian Response to Populism, Amitai Etzioni assigns a central place to the issues of ethics, which is considered in an applied way and in various aspects, taking into account the current global and local challenges of specific societies. This book provides a liberal communitarian response to the rise of populism occurring in many democracies. It highlights the role of communities next to that of the state and the market. The Journal of Economic Sociology publishes the second chapter, which provides a brief overview of diverse perspectives on human nature in various social sciences (economics, sociology, anthropology, and psychology). The author believes that the main problem of the social sciences is that they ignore the idea of a moral fighter. The idea of a moral fighter presupposes an approach according to which a person is involved in an irreconcilable conflict between the search for happiness and the desire to live in accordance with their moral values, which generates a sense of self-affirmation in a person. According to Etzioni, much of the dynamics of human behavior reflects this conflict between the desire for pleasure and the desire for self-affirmation. In this regard, the author believes that the inclusion in social sciences of the idea of a moral fighter, which is present in key religions, would help to advance scientific understanding of what makes people better in society. Source: Etzioni A. (2018) Happiness Is the Wrong Metric: A Liberal Communitarian Response to Populism, New York: Springer. 304 p.